2021
DOI: 10.1001/jamaoto.2020.4471
|View full text |Cite
|
Sign up to set email alerts
|

Physician Confidence in Neck Ultrasonography for Surveillance of Differentiated Thyroid Cancer Recurrence

Abstract: IMPORTANCE Neck ultrasonography, a mainstay of long-term surveillance for recurrence of differentiated thyroid cancer (DTC), is routinely used by endocrinologists, general surgeons, and otolaryngologists; however, physician confidence in their ability to use ultrasonography to identify lymph nodes suggestive of cancer recurrence remains unknown.OBJECTIVE To evaluate physicians' posttreatment surveillance practices for DTC recurrence, specifically their use of and confidence in ultrasonography. DESIGN, SETTING,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Therefore, it is of great importance to explore the methods for early diagnosis and treatment of TC. At present, the clinical treatment options for patients with TC mainly include initial thyroidectomy, radioiodine therapy, and long-term suppression of thyroid-stimulating hormone (TSH)[ 3 - 5 ]. TSH is a glycoprotein hormone synthesized and secreted by thyroid cells in the anterior pituitary gland and plays a regulatory role by acting on the thyrotropin receptor (TSHR) on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great importance to explore the methods for early diagnosis and treatment of TC. At present, the clinical treatment options for patients with TC mainly include initial thyroidectomy, radioiodine therapy, and long-term suppression of thyroid-stimulating hormone (TSH)[ 3 - 5 ]. TSH is a glycoprotein hormone synthesized and secreted by thyroid cells in the anterior pituitary gland and plays a regulatory role by acting on the thyrotropin receptor (TSHR) on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Over 80% of thyroid cancer patients present with well-differentiated thyroid cancer which includes papillary and follicular tumours [ 2 ]. After initial surgery and adjuvant treatment, these patients are often followed indefinitely by an endocrinologist who monitors for cancer recurrence through periodic blood tests and neck ultrasounds [ 3 ]. However, with the rising incidence of thyroid cancer, the increased need for post-treatment follow-up among survivors, and the limited number of thyroid cancer specialists; there is the opportunity for primary care physicians (PCP) to play a larger role in providing follow-up care.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that only 1 in 5 physicians reported having high confidence in their own ability to use ultrasonography to detect lymph nodes suggestive of recurrence; 3 in 5 reported having high confidence in a radiologist's ability to detect recurrence; and 1 in 3 did not have high confidence in either their own or a radiologist's ability to detect recurrence. 3 As with many other aspects of clinical practice, confidence increases with expertise, resources, and experience. Since only 27% of the physicians in the study by Kovatch and colleagues 3 reported performing ultrasonography themselves, we are not surprised by their low confidence.…”
mentioning
confidence: 99%
“…3 As with many other aspects of clinical practice, confidence increases with expertise, resources, and experience. Since only 27% of the physicians in the study by Kovatch and colleagues 3 reported performing ultrasonography themselves, we are not surprised by their low confidence. Those who have elected to have a radiologist obtain and interpret the ultrasonography images may feel daunted by the complexity of detecting suggestive findings or by the high number of neck nodes, which could reduce sensitivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation